What Does It Mean to be well? Understanding the Acehnese Youth Refugees’ Resettlement Experience - Fairuziana Humam; Traci Weinstein; Holly Angelique (Antropologi Indonesia, 2017)
This qualitative study describes the extent to which there is a perception of wellbeing among Acehnese refugees who arrived as adolescents to the United States and settled in the Mid - Atlantic States. Aceh is a province in Northwestern Indonesia consisting of approximately four million people. During 1990 to 2005, approximately 20,000 people left the province due to political conflict to seek asylum in Malaysia, their neighboring country, before resettling in a third country. The participants in this research study are Acehnese refugees that were resettled to the United States as adolescents during that peak migration phase. Results describe how these Acehnese refugees perceive their resettlement with regards to wellbeing, in general, and the development of their identities, sense of belonging and ecological systems of support, specifically. The results of this study shed light on how these Acehnese refugees perceive the many changes in their wellbeing from the early days of their arrival to present day. This study contributes to the literature on refugee studies, highlighting the developmental transition from childhood to adulthood and, at the same time, the cultural transition from home country to host country.Keywords: Acehnese refugees, wellbeing, sense of belonging, identity, ecological systems of support